Comparative study beetwen Netherlands and Romania - Alexandra-Marina Brătulescu (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 7th Edition of the International Symposium, November 2016, Bucharest, 2016)
Agricultural consulting is represent a professional counseling and to request involvement. The farmers and people interested in agriculture can consult specialists or authorized organizations to obtain support in actions undertaken, solving problems or achieving goals. Communication is key in terms of agricultural advisory used as a tool for introducing changes in behavior and attitude of farmers. To the extent that farmers are convinced that to realize and advisory services serves their interests, the effect will be directly proportional to it.
Keywords: 330; agricultural consulting; communication; LVD; rural development; counseling